Selection of elite seedling clones of mango (Mangifera indica L.) exposed by phylogenetic relationship and morpho-taxonomic traits - Singh, A.; Sharma, N.; Nath, V.; Pandey, S.D.; Kumar, K.K.; Reddy, B.M.C.; Sthapit, B.R. (WFL, 2016)
Almost all the current commercial mango cultivars in India are the result of selection from the natural seedling population and majority of them have been selected by the farmers.The conventional breeding system with traditional knowledge is evolving more and more towards preservation of genetic diversity. In Pusa site of the UNEP/GEF sponsored project in the Bihar state of India, many mango seedlings are found growing in the orchards as well as in the backyards. Mango being a highly cross-pollinated fruit crop exhibits a lot of variability in morpho-physico-chemical traits of fruits in these seedling plants. For selection of the elite seedling genotypes, farmers play an important role and with the help of the breeder they can pave the way for maintaining the local germplasm. Hence, in order to study the genetic variability among mango seedlings and to select elite mango genotypes and to conserve them, a survey was conducted in the four project communities and the surrounding villages. A total of 74 seedling types of mango were characterized using morpho-taxonomic parameters. Physico-chemical characterization of fruit samples revealed the existence of a great variability in the seedling mango plants, which not only contributes to biological diversity, but can also be used for crop improvement or for varietal selection. Based on this physico-chemical characterization, principal component and cluster analysis and grouping of seedling clones on the basis of possession of desirable characters by them, six seedling clones, having the majority of desirable fruit characteristics were selected. These selected clones will definitely broaden the genetic base of mango in the Pusa site as well offer the scope for choice of selection of varieties by the farmers and ultimately the conservation of the valuable germplasm.